The Use of Muskox Kill Sites as Temporary Rendezvous Sites by Arctic Wolves with Pups in Early Winter - Gray, David R. (ARCTIC, 1993)
Packs of arctic wolves, Canis lupus arctos, travelling with pups were seen in August or September in Polar Bear Pass, Bathurst Island, Northwest Territories, in five of eight years of field observations. One pack with five pups was observed in 1977 over a period of 19 days. The activity of the pack was centred around the sites of two recently killed muskoxen. Adults took pups to a new kill only the day after the kill but did regurgitate meat for them within 2 hours. Adults and pups continued to use kill sites for up to 8 days after depletion of food available at the carcass. Pups were left on their own at the sites for 8-55 hours at a time. The pups travelled without adults between the kill sites and up to 5 km away at rates varying from 2.5 to 10 km/h. Pups travelled as fast as 11 km/h over longer distances when with adults. The observed time of extensive travel with the pack was earlier than for most southern wolves. The use of kills as temporary rendezvous sites after the pack has begun travelling provides not only a place to meet, but allows pups to rest, feed, explore, and gain experience while adults continue hunting.Key words: wolf, Canis lupus arctos, development of pups, rendezvous sites, homesites, muskoxen (Ovibos moscharus), Polar Bear Pass, Bathurst Island, Northwest Territories Pendant 5 des 8 années durant lesquelles on a mené des observations sur le terrain, dans la vallée Polar Bear, située dans l'île de Bathurst (Territoires du Nord-Ouest), on a aperçu des bandes de loups arctiques, Canis lupus arctos, se déplaçant avec des louveteaux durant les mois d'août et de septembre. En 1977, on a observé une bande avec 5 louveteaux durant 19 jours. Les activités de la bande gravitaient autour des sites où se trouvaient les cadavres de 2 boeufs musqués récemment tués. Les adultes ont emmené les louveteaux auprès d'une nouvelle proie seulement le jour après l'avoir abattue, mais ils ont régurgité la viande pour leurs petits dans les 2 heures qui ont suivi la mort de l'animal. Les adultes et les petits ...